Reform of Mortgage Execution Through Auction in the Context of Seized Collateral (AYDA) by Banks - Hanif Fonda; Boy Nurdin (Journal of Social Research, 2024)
This research aims to analyze the management of Seized Collateral (AYDA) and auction procedures applied by banks in dealing with non-performing loans. Through a normative juridical approach, this study explores the impact of AYDA on market value and bank liquidity, as well as the challenges faced in the auction execution, including low buyer participation and bureaucratic constraints. The results show that effective management of AYDA can reduce the level of Non-Performing Loan (NPL), while optimal auction procedures can maximize collateral value and minimize the risk of losses. Policy recommendations are proposed to enhance the effectiveness of AYDA management and formulate more efficient auction procedures, with the hope of contributing positively to bank financial stability and the economy.